Osteomyelitis Risk Factors Related to Combat Trauma Open Femur Fractures: A Case–Control Analysis. Issue 4 (April 2019) - Lewandowski, Louis R.; Potter, Benjamin K.; Murray, Clinton K.; Petfield, Joseph; Stinner, Daniel J.; Krauss, Margot; Weintrob, Amy C.; Tribble, David R.
Abstract : Objectives: To identify the risk factors for osteomyelitis development in US military personnel with combat-related, open femur fractures? Design: Retrospective observational case–control study. Setting: US military regional hospital in Germany and tertiary care hospitals in United States (2003–2009). Patients/Participants: One hundred three patients with open femur fractures who met diagnostic osteomyelitis criteria (medical record review verification) were classified as cases. Sixty-four patients with open femur fractures who did not meet osteomyelitis diagnostic criteria were included as controls. Main Outcome Measurements: The main outcome measurements were multivariable odds ratios (ORs) and 95% confidence interval (CI). Results: Among patients with surgical implants, osteomyelitis cases had significantly longer time to definitive orthopaedic surgery compared with controls (median: 21 vs. 13 days). Independent predictors for osteomyelitis risk were Gustilo–Anderson classification (transfemoral amputation OR: 19.3; CI: 3.0–123.0) and Orthopaedic Trauma Association Open Fracture Classification for muscle loss (OR: 5.7; CI: 1.3–25.1) and dead muscle (OR: 32.9; CI: 5.4–199.1). Being injured between 2003 and 2006, antibiotic bead use, and foreign body plus implant(s) at fracture site were also risk factors. Conclusions: Patients with open femur fractures resulting in significant muscle damage have the highest osteomyelitis risk. Foreign body contamination was only significant when an implant was present. Increased risk with antibiotic bead use is likely a surrogate for clinical suspicion of contamination with complex wounds. The timeframe association is likely due to changing trauma system patterns around 2006–2007 (eg, increased negative pressure wound therapy, reduced high-pressure irrigation, decreased crystalloid use, and delayed definitive internal fixations). Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.